2008
DOI: 10.1002/macp.200800232
|View full text |Cite
|
Sign up to set email alerts
|

Micellar Structures of Hydrophilic/Lipophilic and Hydrophilic/Fluorophilic Poly(2‐oxazoline) Diblock Copolymers in Water

Abstract: Amphiphilic poly(2‐alkyl‐2‐oxazoline) diblock copolymers of 2‐methyl‐2‐oxazoline (MOx) building the hydrophilic block and either 2‐nonyl‐2‐oxazoline (NOx) for the hydrophobic or 2‐(1H,1H′,2H,2H′‐perfluorohexyl)‐2‐oxazoline (FOx) for the fluorophilic block were synthesized by sequential living cationic polymerization. The polymer amphiphiles form core/shell micelles in aqueous solution as evidenced using small‐angle neutron scattering (SANS). Whereas the diblock copolymer micelles with a hydrophobic NOxn block … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 68 publications
3
61
0
Order By: Relevance
“…When the location of the tracer was changed from being attached to the hydrophobic or hydrophilic block, similar results were obtained [55]. It was demonstrated by small angle neutron scattering that the poly(MeOx-b-NonOx) copolymers self-assemble into spherical core-shell micelles with the core consisting of stretched poly(NonOx) blocks and the corona consisting of coiled poly(MeOx) blocks [56,57]. The micellization of poly(EtOx-b-NonOx) in biphasic waterionic liquid mixtures was studied by Schubert and coworkers [58].…”
Section: à5mentioning
confidence: 52%
“…When the location of the tracer was changed from being attached to the hydrophobic or hydrophilic block, similar results were obtained [55]. It was demonstrated by small angle neutron scattering that the poly(MeOx-b-NonOx) copolymers self-assemble into spherical core-shell micelles with the core consisting of stretched poly(NonOx) blocks and the corona consisting of coiled poly(MeOx) blocks [56,57]. The micellization of poly(EtOx-b-NonOx) in biphasic waterionic liquid mixtures was studied by Schubert and coworkers [58].…”
Section: à5mentioning
confidence: 52%
“…Depending on the relative content of the p n NonOx blocks, the size and the morphology of the surface micelles could be varied. Jordan, Papadakis and co-workers investigated the micellar structures of amphiphilic diblock copolymers synthesized by sequential CROP of MeOx as hydrophilic and either n NonOx as hydrophobic or (9F) n HxOx as fluorophilic part [172]. The copoly(2-oxazoline)s formed core/shell micelles in aqueous media.…”
Section: Self-assembly Of Diblock Copoly(2-oxazoline)smentioning
confidence: 99%
“…Structural formula of bipyridine-functionalized poly(2-oxazoline)s that can be used as macroligands in atom-transfer radical polymerizations (bottom; for details, see reference [172]). …”
Section: Scheme 14mentioning
confidence: 99%
“…Amphiphilic block copoly(2-oxazoline)s with a poly(2-perfluoroalkyl-2-oxazoline) hydrophobic block were demonstrated by Nuyken to aggregate into micellar structures in aqueous solution [80]. To circumvent the very low nucleophilicity of perfluoralkyl oxazoline monomers that decelerate the polymerization, Jordan and Papadakis et al reported the polymerization of 2-fluoroalkylethyl-2-oxazoline monomers where the strong electron withdrawing perfluoroalkyl chain is decoupled from the 2-oxazoline ring [81]. Amphiphilic block copolymers of MeOx with fluorinated monomers were prepared, which self-assembled into micelles with an elongated core-shell structure, presumably due to the high stiffness of the perfluorinated chain and the strong segregation from the water phase.…”
Section: Micellesmentioning
confidence: 99%